Land tenure and economic development, a study of the economic consequences of land registration in Kenya's smallholder areas - Wilson, R. J. A. (Statistical and Social Inquiry Society of Ireland, 1971)
This paper presents some of the findings from a research project for the Queen's University of Belfast which aimed at examining the interrelationship between land tenure reform and economic change with reference to a developing country. It was decided to study in detail the effects of one type of land reform, namely land registration. Registration and grant of title has received considerable attention in Northern Ireland recently, especially since the publication of the Lowry report, and the decision to introduce a compulsory system of registration for all land involved in dealings, which will lead to the eventual registration of all land in the Province. An excellent summary of the historical background to land registration is contained in the Lowry report (Chapter II), and the distinction between registration of deeds and registration of title is clearly explained.
Read before the Society, 26 April 1971
Keywords: Land tenure; Land use; Economic development; Kenyan land reform; 314.15